2023
DOI: 10.1265/ehpm.22-00242
|View full text |Cite
|
Sign up to set email alerts
|

How adverse and benevolent childhood experiences influence depression and suicidal ideation in Chinese undergraduates: a latent class analysis

Abstract: Background: There has been minimal research on the role of benevolent childhood experiences (BCEs) and how such events may offer protection from the insidious effects of adverse childhood experiences (ACEs) or later in life.Objectives: This research aims to learn how BCEs and ACEs interact to affect adolescents' psychological distress. Methods: Cross-sectional survey was conducted in three cities (Xuzhou, Nanjing, and Wuhan) in China from March 2021 to May 2021. Latent class analysis (LCA) was used to classify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The study recommended the development of intervention strategies encompassing adverse childhood experiences, economic factors, and mental health. It also uncovered the positive impact of favorable childhood experiences on mental health [ 51 ]. Another meta-analysis demonstrated the effectiveness of cognitive behavioral therapy in alleviating depressive symptoms among adolescents [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study recommended the development of intervention strategies encompassing adverse childhood experiences, economic factors, and mental health. It also uncovered the positive impact of favorable childhood experiences on mental health [ 51 ]. Another meta-analysis demonstrated the effectiveness of cognitive behavioral therapy in alleviating depressive symptoms among adolescents [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bethell et al (2019) also found that higher PCEs predicted lower odds of depression/poor mental health. Other mental health outcomes included lower suicidal ideation and attempts Kuhar & Kocjan, 2021;Tang et al, 2023;Narayan et al, 2023a), lower symptoms of and higher remission from personality disorders (Gunay-Oge et al, 2020b;Skodol et al, 2007), lower disturbances from complex PTSD symptoms (Karatzias et al, 2020), lower severity of global mental health symptoms (Rodriguez et al, 2021), and higher self-ratings of mental health (Kuhar & Kocjan, 2021). Higher PCEs were also linked to lower prenatal psychopathology, including lower thought problems, detachment, and disinhibited externalizing behaviors (Clark et al, 2023).…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…The European Union and Occupational Safety and Health Administration(OSHA) regulations stipulate a marginal value for wood dust exposure level [ 5 ], and such regulation is single 8-hour time weighted average(TWA) of 5 mg/m 3 and a short term exposure limit(STEL) of 10 mg/m 3 for all hard wood and soft wood dusts [ 6 ]. Occupational exposure to wood dust has been linked to a variety of respiratory disorders, including asthma, allergic rhinitis, chronic bronchitis, and lung function impairment [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%